2019
DOI: 10.1111/den.13468
|View full text |Cite
|
Sign up to set email alerts
|

Impact of electrical pulse cut mode during endoscopic papillectomy: Pilot randomized clinical trial

Abstract: ObjectiveEndoscopic papillectomy is increasingly being used for ampullary adenoma treatment. However, it remains challenging despite increased safety with treatment advances. The ideal power output and electrosurgical current mode for mucosal resection are not established. We aimed to identify the ideal electrical pulse for use during resection.MethodsThis pilot randomized, single‐blind, prospective, multicenter trial, recruited patients with ampullary adenomas and conventional anatomy who were scheduled to un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 43 publications
0
23
0
Order By: Relevance
“…Another consideration is that electrosurgical current mode for mucosal resection can affect bleeding after papillectomy. Iwasaki et al 31 . showed that the Endocut mode may prevent immediate bleeding in cases with large tumor sizes, albeit at the cost of more frequent crush artifacts.…”
Section: Discussionmentioning
confidence: 99%
“…Another consideration is that electrosurgical current mode for mucosal resection can affect bleeding after papillectomy. Iwasaki et al 31 . showed that the Endocut mode may prevent immediate bleeding in cases with large tumor sizes, albeit at the cost of more frequent crush artifacts.…”
Section: Discussionmentioning
confidence: 99%
“…The rate of crush artefacts was higher in the endocut than in the autocut group (27 % vs. 3.3 %, P = 0.03). Immediate bleeding when tumors greater than 14 mm in diameter were resected was more common in the autocut than in the endocut group (88 % vs. 46 %, P = 0.04) [169].…”
Section: Recommendationmentioning
confidence: 90%
“…In a retrospective case-control trial focusing on adverse events with respect to technical modifications of papillectomy, the use of endocut instead of pure cutting current resulted in a significant reduction of early bleeding without any consequence observed in terms of cannulation rate of the pancreatic orifice and post-ERCP pancreatitis rate [154]. Iwasaki et al [169] in an RCT demonstrated that although both pure cutting current (autocut mode) and blended cutting current (endocut mode) have similar efficacy and safety for endoscopic papillectomy, the endocut mode may prevent immediate bleeding in cases with large tumor sizes. In this study, 60 patients were enrolled over a 2-year period.…”
Section: Recommendationmentioning
confidence: 99%
“…In our series, the vertical margin was uncertain in three cases due to the burning effects but no tumor recurrence was observed after a median follow-up of 244 days. In a pilot randomized controlled trial comparing electrical pulse cut mode, the Autocut mode without coagulation might prevent these burning effects and allow better pathological evaluation [21].…”
Section: Discussionmentioning
confidence: 99%